Effect of natural ageing on physiological and biochemical behavior of onion(Allium cepa) seeds having differential initial seed quality - PAL, NARENDER; BASU, SUDIPTA; ANAND, ANJALI; KHAR, ANIL; JHA, SHAILENDRA KUMAR; YALAMALLE, VISHWANATH; SAHOO, MONALISHA; LAL, SANDEEP KUMAR (The Indian Journal of Agricultural Sciences, 2025)
Onion (Allium cepa L.) seeds are short-lived and the seed quality deteriorates during storage. The understanding of seed deterioration associated with the ROS content along with the antioxidant enzyme activities specifically in relation with initial seed germination potential is not available. A study was carried out during 2022 and 2023 at ICAR-Indian Agricultural Research Institute, New Delhi to assess the biochemical behaviour of onion seeds having differential initial germination percentage, under ambient storage condition. Freshly harvested seeds of four onion genotypes i.e. Sukhsagar, POS 24K, Bhima Super and Bhima Shubhra, having different initial seed germination percentage ranging from 84–96 % were stored under ambient conditions for 12 months. The seed germination declined, ranging from 49–77 % after 12 months with a percent decline in germination ranging from 19–46%. An increase in the activity of NADPH oxidase, ROS as well as malondialdehyde content and decline in antioxidant enzyme activity was observed in onion seeds after storage. A significant positive correlation was found among germination percentage, catalase, peroxidase and superoxide dismutase activity, whereas germination percentage was negatively correlated with superoxide radical, hydrogen peroxide, MDA content and NADPH oxidase activity. The study implicated the critical role of catalase, peroxidase and superoxide dismutase in ameliorating the negative impact of superoxide radical, hydrogen peroxide that causes deterioration with seed ageing without being affected by initial germination potential.